American economic development - Krooss, Herman.E (Englewood Cliffs, N.J. : Prentice-Hall, 1955)
The book describes American economic development, its causes and consequences, in terms of the changing standard or level of living as measured by the national income.
Includes index
rpm 01/06/2017
Loans
Keywords: United States -- Economic conditions; Economic history; United States